2016
DOI: 10.1128/aac.01177-16
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Sequence Type 235 Pseudomonas aeruginosa Clinical Isolates Producing IMP-26 with Increased Carbapenem-Hydrolyzing Activities in Vietnam

Abstract: Forty clinical isolates of multidrug-resistant Pseudomonas aeruginosa were obtained in a medical setting in Hanoi, Vietnam. Whole genomes of all 40 isolates were sequenced by MiSeq (Illumina), and phylogenic trees were constructed from the single nucleotide polymorphism concatemers. Of these 40 isolates, 24 (60.0%) harbored metallo-␤-lactamase-encoding genes, including bla IMP-15 , bla IMP-26 , bla IMP-51 , and/or bla NDM-1 . Of these 24 isolates, 12 harbored bla IMP-26 and belonged to sequence type 235 (ST235… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 38 publications
1
42
1
Order By: Relevance
“…The selected isolates, consisting of Gram-negative bacteria producing a variety of carbapenemases, were readily available in the two participating laboratories (10)(11)(12)(13)(14)(15)(16)(17). These isolates included 23 GES-5producing isolates obtained throughout Japan and not epidemiologically related; GES-5 producers were included because they have spread and are causing serious problems in medical settings throughout Japan (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…The selected isolates, consisting of Gram-negative bacteria producing a variety of carbapenemases, were readily available in the two participating laboratories (10)(11)(12)(13)(14)(15)(16)(17). These isolates included 23 GES-5producing isolates obtained throughout Japan and not epidemiologically related; GES-5 producers were included because they have spread and are causing serious problems in medical settings throughout Japan (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of tellurium, mercury, and arsenic operons in pEHZJ1 was consistent with the conclusion that IncHI2 plasmids usually harbor toxin-antitoxin systems and heavy metal resistance from, Aoki et al 40 These metal-resistant operons may make the strains carrying IncHI2type plasmid to be more viable in diverse environments. Thus far, two reports have studied the genetic features surrounding bla IMP-26 in P. aeruginosa, 17,18 and one in Enterobacter cloacae. 20 Among them, the genetic context surrounding bla IMP-26 in P. aeruginosa was intI1-bla IMP-26 -qacG-aacA4-aac (6ʹ)-orf-catB3 and intI1-bla IMP-26 -qacG-aac(6ʹ)-Ib-aac(6ʹ)-orf3-orf4-catB3-dfrA1-tnpA-istB-orf5, respectively.…”
Section: Dovepressmentioning
confidence: 99%
“…Previous reports showed that bla IMP-26 has high genetic similarity to bla IMP-4 , with only one position substitution at 145 (G-to-T change), 13 moreover, bla IMP-26 and bla IMP-4 were generally carried by a class 1 integron. 17,18,46 So, we selected pIMP26, pEI1573 and our plasmid pEHZJ1 for comparative analysis of genes surrounding bla IMP-4 and bla IMP-26 . The results revealed that pIMP26 had the same genetic context surrounding bla IMP-26 as pEHZJ1, however genetic environment of bla IMP-4 in pEI1573 was intI1bla IMP-4 -qacG-aacA4-catB-qacEΔ1-sul1.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the bla KPC gene, the IMP-type metallo-β-lactamase (MBL) genes, which have been reported carried by IncL/M, IncA/C, IncHI2, and IncN plasmids in Enterobacterales from Australia and China (Villa et al, 2010;Dolejska et al, 2016;Wang et al, 2017), were not frequently detected in CRKP and associated with IncFII K plasmids (Wang et al, 2018). IMP-26, which differs from IMP-4 by a single amino acid substitution (Phe49Val), was firstly reported from the Pseudomonas aeruginosa isolate in Singapore in 2010 (Koh et al, 2010;Tada et al, 2016) and was demonstrated to possess increased carbapenem-hydrolyzing activity to meropenem than IMP-1 (Tada et al, 2016).…”
Section: Introductionmentioning
confidence: 99%